2011
DOI: 10.1016/j.radonc.2011.05.026
|View full text |Cite
|
Sign up to set email alerts
|

Single vocal cord irradiation: A competitive treatment strategy in early glottic cancer

Abstract: Given the accuracy (1-2mm) and small volume disease (CTV limited to one vocal cord), for the use of stereotactic RT techniques SVCI with large fraction sizes is currently being investigated in clinic. It is argued that hypofractionated SVCI can be a competitive alternative to laser surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 31 publications
0
24
1
Order By: Relevance
“…found a strong correlation between quality of speech and doses to the aryepiglottic folds, pre‐epiglottic space, false vocal cords and lateral pharyngeal walls. The use of IMRT for early glottic cancer has been investigated in several studies and has consistently shown a significant sparing of the carotids . In the era of IMRT and IGRT, it becomes increasingly difficult to argue in favour of whole larynx irradiation in glottic cancer because of fear of laryngeal motion, while the surgical approach proposes a focused resection of tumour bearing vocal cord.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…found a strong correlation between quality of speech and doses to the aryepiglottic folds, pre‐epiglottic space, false vocal cords and lateral pharyngeal walls. The use of IMRT for early glottic cancer has been investigated in several studies and has consistently shown a significant sparing of the carotids . In the era of IMRT and IGRT, it becomes increasingly difficult to argue in favour of whole larynx irradiation in glottic cancer because of fear of laryngeal motion, while the surgical approach proposes a focused resection of tumour bearing vocal cord.…”
Section: Discussionmentioning
confidence: 99%
“…Although swallowing was a rare event, the occurrence of an inadvertent swallowing episode during treatment with the proposed PL‐VMAT margin resulted in a median time of CTV excursion beyond the 95% IDL below 1 second. The group from Erasmus Medical Center Cancer Institute has previously assessed dosimetric feasibility of focal vocal cord irradiation for early‐stage local cancer T1aN0 using 4D‐CT; they showed sparing of contralateral vocal cord and various laryngeal structures compared to conventional radiotherapy . The same group recently published the first clinical outcomes from a retrospective analysis of 30 patients with T1aN0 glottic cancer treated with single vocal cord to a dose of 58 Gy in 16 fractions and showed excellent 2 year LC of 100% .…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, other groups have proposed limiting the treatment volume only to the involved vocal cord to maximize carotid sparing. 20 For example, Janssen and colleagues recently reported excellent local control rates in 39 patients with T1-2N0 glottic carcinoma treated with IMRT, including 21 patients that underwent ipsilateral vocal cord irradiation with bilateral carotid sparing resulting in a mean contralateral carotid dose of 20.2 Gy. 21 Since the time period of this study, we have chosen to employ an intermediate approach, using daily image guidance and decreasing our circumferential margin to 0.5cm, with as little as 0.3cm margin allowable near the carotid arteries in order to achieve a more significant reduction in carotid dose.…”
Section: Discussionmentioning
confidence: 99%
“…Targeting only the involved vocal cord with RT could further improve voice quality, and reduce the radiation exposure of the surrounding OAR. Osman et al (9)(10)(11)(12), Levendag et al (13) and Kwa et al (14) explored the technical feasibility, and dosimetric advantages, of targeting only a single affected vocal cord with IMRT for T1a glottic cancer.…”
Section: Discussionmentioning
confidence: 99%
“…However, to date, few studies have investigated the possibility of changing the target volume. Only one institution in the Netherlands has investigated limiting the IMRT target volume to a single affected vocal cord for T1a glottic cancer (9)(10)(11)(12)(13)(14); their studies revealed that IMRT with a limited target volume was associated with a reduction in the irradiation of adjacent normal tissue. However, the oncological outcomes of limiting the target volume to a single vocal cord throughout the course of RT remain to be elucidated.…”
Section: Introductionmentioning
confidence: 99%